Molecular mechanisms of action of epigallocatechin gallate in cancer: Recent trends and advancement. (May 2022) - Aggarwal, Vaishali; Tuli, Hardeep Singh; Tania, Mousumi; Srivastava, Saumya; Ritzer, Erin E.; Pandey, Anjana; Aggarwal, Diwakar; Barwal, Tushar Singh; Jain, Aklank; Kaur, Ginpreet; Sak, Katrin; Varol, Mehmet; et al.
Abstract: Epigallocatechin gallate (EGCG), also known as epigallocatechin-3-gallate, is an ester of epigallocatechin and gallic acid. EGCG, abundantly found in tea, is a polyphenolic flavonoid that has the potential to affect human health and disease. EGCG interacts with various recognized cellular targets and inhibits cancer cell proliferation by inducing apoptosis and cell cycle arrest. In addition, scientific evidence has illustrated the promising role of EGCG in inhibiting tumor cell metastasis and angiogenesis. It has also been found that EGCG may reverse drug resistance of cancer cells and could be a promising candidate for synergism studies. The prospective importance of EGCG in cancer treatment is owed to its natural origin, safety, and low cost which presents it as an attractive target for further development of novel cancer therapeutics. A major challenge with EGCG is its low bioavailability which is being targeted for improvement by encapsulating EGCG in nano-sized vehicles for further delivery. However, there are major limitations of the studies on EGCG, including study design, experimental bias, and inconsistent results and reproducibility among different study cohorts. Additionally, it is important to identify specific EGCG pharmacological targets in the tumor-specific signaling pathways for development of novel combined therapeutic treatments with EGCG. The present review highlights the ongoing development to identify cellular and molecular targets of EGCG in cancer. Furthermore, the role of nanotechnology-mediated EGCG combinations and delivery systems will also be discussed.